2023
DOI: 10.1371/journal.pmed.1004167
|View full text |Cite
|
Sign up to set email alerts
|

Inequities in COVID-19 vaccine and booster coverage across Massachusetts ZIP codes after the emergence of Omicron: A population-based cross-sectional study

Abstract: Background Inequities in Coronavirus Disease 2019 (COVID-19) vaccine and booster coverage may contribute to future disparities in morbidity and mortality within and between Massachusetts (MA) communities. Methods and findings We conducted a population-based cross-sectional study of primary series vaccination and booster coverage 18 months into the general population vaccine rollout. We obtained public-use data on residents vaccinated and boosted by ZIP code (and by age group: 5 to 19, 20 to 39, 40 to 64, 65+… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…17 Further, a study performed in the US state of Massachusetts showed that first dose and subsequent booster dose was greater in areas with higher income and education and was lower in areas with a greater percentage of Black, Latino and indigenous adults. 22 Additionally, among a specific population of healthcare workers in Wales, booster dose vaccine uptake was consistently lower among black healthcare workers, as well as those from deprived areas. 23 These studies are in line with our results, with lower probability of booster vaccine among individuals with the lowest level of education, lowest disposable household income and those born outside of Sweden as well as in the areas with a low socioeconomic standing.…”
Section: Results In Relation To Previous Studiesmentioning
confidence: 93%
“…17 Further, a study performed in the US state of Massachusetts showed that first dose and subsequent booster dose was greater in areas with higher income and education and was lower in areas with a greater percentage of Black, Latino and indigenous adults. 22 Additionally, among a specific population of healthcare workers in Wales, booster dose vaccine uptake was consistently lower among black healthcare workers, as well as those from deprived areas. 23 These studies are in line with our results, with lower probability of booster vaccine among individuals with the lowest level of education, lowest disposable household income and those born outside of Sweden as well as in the areas with a low socioeconomic standing.…”
Section: Results In Relation To Previous Studiesmentioning
confidence: 93%
“…Numerous countries have expressed concerns regarding disparities in vaccine coverage, highlighting significant social, economic, and racial/ethnic inequalities [11,12]. The situation in Brazil is particularly concerning.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, some individuals at greatest risk, such as the older adult and homebound, were completely unable to access vaccines (7)(8)(9). Beyond technological challenges, equity in vaccine distribution suffered as well, partially related to mass vaccination sites favoring those with access to transportation, those who lived near the vaccination centers, and those without socioeconomic barriers to seeking care at these facilities (10)(11)(12)(13)(14). While Massachusetts was successful in vaccinating a large percentage of its population, a need clearly existed to extend vaccine capability to those with difficulty accessing mass vaccination sites and to ensure equitable distribution of this life-saving measure.…”
Section: Introductionmentioning
confidence: 99%